Analisis Konten Budaya Dari Buku Teks Bahasa Jerman Deutsch Echt Einfach A1.1 - Anugerahing Gusti; Wening Sahayu (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
Teaching German as a foreign language in Indonesia requires the integration of linguistic and cultural aspects to develop students’ intercultural competence. Textbooks play a significant role in representing culture, yet most language learning materials tend to portray culture superficially and selectively. This study aims to analyze the representation of cultural elements in the textbook Deutsch echt einfach A1.1 für Jugendliche using a qualitative descriptive approach and content analysis method. Data were obtained from the book’s textual and visual content, analyzed through the lens of Dweik et al.’s (2015) twelve cultural elements framework. The findings reveal that elements such as food and beverages, social behavior, and family relationships are the most frequently represented. In contrast, deeper cultural elements such as history, politics, religion, ecology, and economy are scarcely present. These results indicate that the textbook focuses primarily on surface-level culture and does not fully support the development of students’ intercultural competence. The implication is that teachers and curriculum developers need to supplement textbooks with more critical, holistic, and contextually relevant cultural materials to enhance foreign language learning.